1998
DOI: 10.1046/j.1365-2249.1998.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 and IL-4 co-operate to normalizein vitroIgA production in IgA-deficient (IgAD) patients

Abstract: In the present study we evaluated in vitro immunoglobulin production from IgAD individuals and healthy controls. Peripheral blood mononuclear cells (PBMC) from IgAD and controls were cultured with anti-CD40 MoAb presented on a CDw32-transfected fibroblast cell line (CD40 system) in the presence of IL-10, IL-2, IL-4, transforming growth factor-beta (TGF-beta) alone as well as of IL-10 in combination with each of the other three cytokines. Only IL-10 added alone induced significant changes in baseline immunoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Patients with IgA deficiency are usually defined by serum IgA levels of Ͻ0.05 g/liter (normal levels are 0.5 to 3.5 g/liter), but many, if not most, IgA-deficient patients have low but detectable levels of serum IgA antibodies (9,30) and can produce IgA antibodies at near-normal levels in vitro (8,23). This is in contrast to the complete lack of IgA production in IgA-deficient mice, which lack crucial gene segments for expressing IgA heavy chains (17).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IgA deficiency are usually defined by serum IgA levels of Ͻ0.05 g/liter (normal levels are 0.5 to 3.5 g/liter), but many, if not most, IgA-deficient patients have low but detectable levels of serum IgA antibodies (9,30) and can produce IgA antibodies at near-normal levels in vitro (8,23). This is in contrast to the complete lack of IgA production in IgA-deficient mice, which lack crucial gene segments for expressing IgA heavy chains (17).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Several authors have demonstrated that B cells from IgAdeficient subjects and CVID patients undergo class-switch recombination (CSR) when stimulated through CD40 (TNFRSF5) together with interleukin-4 (IL-4) or interleukin-10 (IL-10), leading to reconstitution of IgG and IgA production ex vivo. [8][9][10][11][12] However, these effects have not yet been established in vivo and it remains to be seen whether targeting of the CD40 molecule and stimulation with IL-4 and IL-10 are tolerated and therapeutically effective in humans. 13,14 Immunomodulatory intervention with low doses of IL-2 has shown promise in vivo, despite insufficient evidence and proof of safety to support its routine use.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical picture of SIgAD may vary from absence of clinical manifestations to fully symptomatic form (16). A variety of pathologic mechanisms of SIgAD have been postulated, which include the occurrence of IgA-specific T suppressor cells, inadequate T helper (Th) cell function, an intrinsic B-cell defects (17), or decreased expression of CD40 on monocytes (18). In most cases, the molecular defect is unknown, although in some patients with SIgAD, mutations in TACI gene have been identified (11,12).…”
mentioning
confidence: 99%